PENGATURAN PERTANGGUNGJAWABAN PIDANA KOMANDAN MILITER MENURUT PASAL 129 DAN PASAL 132 KUHPM DAN HUBUNGANNYA DENGAN PASAL 403 RUU KUHP DRAFT 10 - DRAJAD BRIMA YOGA, S.Ip. A.21211076, Jurnal Mahasiswa S2 Hukum UNTAN (Jurnal NESTOR Magister Hukum, 2013)
ABSTRACTThis thesis discusses issues Military Commander Settings Criminal Liability Under Section 129 and Section 132 KUHPM and Its Relation to Article 403 of the Criminal Code Draft Bill 10. From the results of research using the method of normative legal research concluded that: 1. Keep in mind the basic Pertangggung He arranged Answer Criminal Military Commander In KUHPM, the Law Court of Human Rights and the Draft Criminal Code is based on the doctrine of